Relief for Prison Overcrowding: Evaluating Michigan's Accelerated Parole Statute - Judge, Frank T. (1982)
This Note describes and analyzes Michigan's Prison Overcrowding Emergency Powers Act. Part I reviews briefly current efforts to relieve prison overcrowding and concludes that traditional remedies are largely inadequate. Part II examines the early prisoner release statute and its implementation. Finally, Part III evaluates the statute's success in relieving prison overcrowding